Leprosy As a Complex Infection: Breakdown of the Th1 and Th2 Immune Paradigm in the Immunopathogenesis of the Disease - de Sousa, Jorge Rodrigues; Sotto, Mirian Nacagami; Simões Quaresma, Juarez Antonio (Frontiers in Immunology, 2017)
Leprosy is a chronic infectious disease whose evolution involves complex immune mechanisms of the host that influence the clinical presentation of the disease. For many years, the main interpretation of the host defense response was based on characterization of the established immune paradigm between T helper (Th) 1 and Th2 lymphocytes. However, with advances in the knowledge of immunology, new approaches have emerged along with the development of new immunological pathways that have changed the interpretation of the long-established paradigm of the polar forms of the disease, especially with the identification of new subtypes of T lymphocytes such as Th9, Th17, Th22, and Tregs. Thus, this review discusses the role of these new subtypes of T helper lymphocytes and how the development of the immune response of these cells modifies the pattern of the Th1/Th2 response in the immunopathogenesis of leprosy.